1989
DOI: 10.1038/bjc.1989.87
|View full text |Cite
|
Sign up to set email alerts
|

Squamous carcinoma of the oesophagus: histological criteria and their prognostic significance

Abstract: Summary One hundred resected cases of squamous cell carcinomas of the oesophagus were reviewed and a series of histological criteria related to the survival time. Two histological features were important in the assessment of survival. Good prognostic factors were a marked lymphocytic response to the tumour and a lack of intravenous tumour infiltration. Presence of tumour in the middle third of the oesophagus, infiltration through the muscularis propria, severe tumour necrosis, glandular or small cell tumour di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…Robey-Cafferty et al 19 examined 69 patients with squamous cell carcinoma of the oesophagus and showed that grade was an independent prognostic determinant. In contrast, Edwards et al 6 found no association between differentiation and survival. More recently, studies of adenocarcinoma have been inconsistent concerning the prognostic significance of tumour differentiation 16,20 .…”
Section: Discussionmentioning
confidence: 90%
“…Robey-Cafferty et al 19 examined 69 patients with squamous cell carcinoma of the oesophagus and showed that grade was an independent prognostic determinant. In contrast, Edwards et al 6 found no association between differentiation and survival. More recently, studies of adenocarcinoma have been inconsistent concerning the prognostic significance of tumour differentiation 16,20 .…”
Section: Discussionmentioning
confidence: 90%
“…Two studies of squamous cell carcinoma patients documented a significant survival advantage in those who demonstrated a prominent "inflammatory response" to their tumors. 31,32 In several large studies of colon carcinoma patients, these features have been shown to be independently and significantly associated with better survival by Harrison et al, Graham and Appelman, and Jass et al 17,[27][28][29] Immunophenotypic studies of lymphoid infiltrates in colon carcinoma have documented a predominance of T4 lymphocytes and macrophages, whereas the lymphoid follicles in the CLR have been shown to represent a mixture of T4 and T8 lymphocytes, Ia positive lymphocytes, and macrophages. [33][34][35] To our knowledge, phenotypic studies of lymphoid infiltrates have not been performed in esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the dichotomy between our results and those of Dexter et al reflects the somewhat confused nature of the literature on the topic of prognostic markers in oesophageal cancer. Although a large number of studies have been conducted on this subject, there is conflicting evidence as to the prognostic importance of many factors such as T-stage (Patti and Owen, 1997;Dexter et al, 2001), tumour type (Dexter et al, 2001;Siewert et al, 2001) and tumour grade (Edwards et al, 1989;Robey-Cafferty et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the management of oesophageal cancer, survival following oesophagectomy remains poor with a 5-year survival of approximately 25% (Alexiou et al, 1998; Ellis, 1999). A number of studies (Edwards et al, 1989;Robey-Cafferty et al, 1991;Patti and Owen, 1997) have attempted to identify histological characteristics that correlate with long-term postoperative survival. The presence of microscopic tumour at the circumferential margin of excision is one such histological factor that has recently been investigated as a possible prognostic marker.…”
mentioning
confidence: 99%
See 1 more Smart Citation